2003
DOI: 10.1192/bjp.183.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic evaluation of computer-aided self-help for anxiety and depression

Abstract: Computer-aided self-help is a 'clinician extender'that greatly cuts per-patient therapist time without impairing improvement. It could reduce the per-patient cost of CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 20 publications
7
124
0
2
Order By: Relevance
“…Five of the papers reported uncontrolled before-and-after studies, [265][266][267][268][269] only one included a (non-randomised) historical control. 270 Study quality was poor (range 15-18), failings being due to lack of information on intervention (n = 3), description of principal confounders (n = 6) and whether or not treatment was representative of treatment the majority of patients received (n = 6).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of the papers reported uncontrolled before-and-after studies, [265][266][267][268][269] only one included a (non-randomised) historical control. 270 Study quality was poor (range 15-18), failings being due to lack of information on intervention (n = 3), description of principal confounders (n = 6) and whether or not treatment was representative of treatment the majority of patients received (n = 6).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…All studies reported improved depression and anxiety post intervention, both in terms of changes in mean score greater than the defined clinically important difference and in the proportion of people who improved during the course. [265][266][267][268][269] At the end of the course, approximately one in five of those who completed the cCBT were referred on to face-to-face therapy. 268 Authors concluded that offering cCBT as a first step was an effective way to manage demand, 265,267,268 provide timely access to therapy 269 and could be supported by volunteer support workers (as opposed to mental health professionals).…”
Section: Primarily Patient Education With or Without Organisational mentioning
confidence: 99%
See 3 more Smart Citations